Pengaruh CSR, GCG, dan Capital intensity Terhadap Tax Avoidance - Farizah Nur Amalia; Tantina Haryati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to demonstrate the impact of CSR, GCG (independent commissioners and audit committees), and capital intensity on tax evasion techniques using firm size as a moderator. This study focuses on property and real estate firms that were listed in the IDX from 2019 to 2022. The study collected samples using the purposive sampling approach, with a total of 52 samples. In this work, a quantitative method was used, with PLS-SEM data analysis performed using the SmartPLS 3 tool. The study's findings indicate that while CSR and independent commissions have no effect on tax avoidance, audit committees and capital intensity do have an impact. Next, the size of the company as a moderating variable can influence the relationship between CSR and the audit committee on tax avoidance, but the size of the company cannot influence the relationship between independent commissions and modal intensity on tax avoidance.